Communication surrounding initiation and withdrawal of non-invasive ventilation in adults with motor neurone disease. (2nd July 2022) - Chapman, Charlotte; Bayes, Sara; Sim, Moira
Abstract : Background: Motor neurone disease causes respiratory weakness that can lead to death. While non-invasive ventilation relieves symptoms, there are complex issues to consider prior to commencement. Aim: To identify what is known and understood about the clinician communication of non-invasive ventilation by people with motor neurone disease. Method: The Joanna Briggs Institute approach to systematic reviews was followed for literature retrieval and selection. Data sources: Research literature published between 1990–2019 in English from the Medline, CINAHL, ProQuest Research Library and the Cochrane Library of Systematic Reviews databases were used. Results: A total of two themes emerged: communication challenges doctors face when discussing non-invasive ventilation withdrawal, and the importance of well-timed, effective communication by clinicians–specifically the influence clinicians have on family decision-making. Conclusions: Guidance on communications around palliative care, non-invasive ventilation introduction and withdrawal exist, however implementation is often not straightforward. Research into the communication surrounding non-invasive ventilation from those living with motor neuron disease, their families and clinicians is required to inform guideline implementation and practice.